Are we measuring the same thing? Psychometric and research considerations when adopting new testing modes in the time of COVID‐19. Issue 2 (19th October 2020) - Booth, Tom; Murray, Aja; Muniz‐Terrera, Graciela
Abstract: As the world navigates unchartered territories and witnesses the overwhelming impact of COVID‐19, investigators face important challenges to ensure continuity of research studies in a scientifically sound manner. Given the susceptibility of the older population to COVID‐19, research in the field of aging and dementia may be more severely impacted than other areas. With in‐person testing halted, researchers are considering remote testing to collect data on questionnaires and functioning, including cognitive functioning. This is not without challenges. Here, we discuss psychometric properties of the scales that need to be considered and evaluated when implementing remote testing to ensure the quality of the studies is preserved. We encourage the community to join efforts to improve practice sharing and facilitating access to item‐level data.